2015
DOI: 10.1007/s10620-014-3469-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus, and Not Obesity, Is Associated with Lower Survival Following Liver Transplantation

Abstract: In conclusion, obesity alone was not associated with lower post-transplant survival. However, DM, either alone or comorbid with obesity, is associated with significantly greater post-transplant mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
3
35
1
Order By: Relevance
“…To our knowledge, this is the first nationwide population-based study to investigate the effects of DM on the risk of post-LTx mortality and morbidity in an Asian population. Contrary to the previous publications [13][14][15][16], we observed that DM patients did not exhibit increased risks of early post-LTx morbidities or mortality compared with non-DM patients. However, further analysis showed that preexisting DM with renal manifestations was associated with a significantly higher mortality rate within 90 days after LTx, in comparison with the non-DM cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first nationwide population-based study to investigate the effects of DM on the risk of post-LTx mortality and morbidity in an Asian population. Contrary to the previous publications [13][14][15][16], we observed that DM patients did not exhibit increased risks of early post-LTx morbidities or mortality compared with non-DM patients. However, further analysis showed that preexisting DM with renal manifestations was associated with a significantly higher mortality rate within 90 days after LTx, in comparison with the non-DM cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, some studies have evaluated the risk of perioperative mortality and complications after LTx in DM patients in a population-based setting [13][14][15][16]. However, there has been no similar study in an Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…Such patients may be disproportionately affected by subclinical cardiac disease and a blunted cardiovascular response to the hemodynamic stress of LT resulting in arrhythmia and incident heart failure. Third, over the past decade there has been a marked rise in the prevalence of CVD comorbid conditions, such as diabetes, among LT candidates related to the ongoing obesity epidemic in the United States(8, 9). In fact, it is well established that nonalcoholic steatohepatitis (NASH), an obesity-related cause of end-stage liver disease that is associated with increased CVD morbidity and mortality(10, 11), is likely to become the most common indication for LT over the next decade(12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…46 Up to 46% of patients will develop post-LT metabolic syndrome, with the greatest risk seen in those with BMI of 30 kg/m 2 or greater pre-LT. 43,44,46 Pretransplant obesity has been shown to be a strong risk factor for posttransplant weight gain 47,48 ). Even among 37 obese cirrhotic patients enrolled in an intensive pretransplant weight loss program (and who achieved target BMI <35 kg/m 2 ), 60% gained weight to a BMI greater than 35 kg/m 2 after LT. 18 Posttransplant obesity (class II or greater) increases the risk of posttransplant diabetes, a strong predictor of decreased survival after LT, 49,50 as well as post-LT nonalcoholic steatohepatitis. 47 The risk of new onset DM may be further heightened by corticosteroids and/or calcineurin-inhibitor use.…”
Section: Posttransplant Considerationsmentioning
confidence: 99%